2010
DOI: 10.1016/j.bpj.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

All-or-None versus Graded: Single-Vesicle Analysis Reveals Lipid Composition Effects on Membrane Permeabilization

Abstract: We report a single-vesicle approach to compare the all-or-none and graded mechanisms of lipid bilayer permeabilization by CpreTM and NpreTM, two peptides derived from the membrane-proximal external region of the HIV fusion glycoprotein gp41 subunit. According to bulk requenching assays, these peptides permeabilize large unilamellar vesicles via all-or-none and graded mechanisms, respectively. Visualization of the process using giant unilamellar vesicles shows that the permeabilization of individual liposomes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 54 publications
3
76
0
Order By: Relevance
“…Following incubation of PI(4,5)P 2 containing GUVs with FGF2-Y82pCMF, a substantial fraction of about 40% of total GUVs was characterized by high luminal fluorescence (Ն80% compared with the surroundings), indicating that the fluorescent tracer had equilibrated between the lumen and the surroundings of the vesicles. This behavior is typical for an "all-or-none" mechanism of protein-dependent membrane activity (42). Quantification of control experiments using GUVs either lacking PI(4,5)P 2 or containing the Ni-NTA lipid revealed that, following incubation with FGF2-Y82pCMF, only a minor population contained the fluorescent tracer (Fig.…”
Section: Pi(45)p 2 -Dependent Oligomerization Of Fgf2 On Membranementioning
confidence: 76%
See 1 more Smart Citation
“…Following incubation of PI(4,5)P 2 containing GUVs with FGF2-Y82pCMF, a substantial fraction of about 40% of total GUVs was characterized by high luminal fluorescence (Ն80% compared with the surroundings), indicating that the fluorescent tracer had equilibrated between the lumen and the surroundings of the vesicles. This behavior is typical for an "all-or-none" mechanism of protein-dependent membrane activity (42). Quantification of control experiments using GUVs either lacking PI(4,5)P 2 or containing the Ni-NTA lipid revealed that, following incubation with FGF2-Y82pCMF, only a minor population contained the fluorescent tracer (Fig.…”
Section: Pi(45)p 2 -Dependent Oligomerization Of Fgf2 On Membranementioning
confidence: 76%
“…Analysis of PI(4,5)P 2 and Tyrosine Phosphorylation-dependent Membrane Activity of FGF2 Oligomers Employing Giant Unilamellar Vesicles and Confocal Microscopy-To directly visualize the membrane activity of FGF2-Y82pCMF, we employed GUVs combined with confocal microscopy (42). Three types of GUVs with a plasma membrane-like lipid composition either lacking PI(4,5)P 2 , containing PI(4,5)P 2 (plasma membrane ϩ PIP 2 ), or containing the Ni-NTA lipid (plasma membrane ϩ nickel) were generated (Fig.…”
Section: Pi(45)p 2 -Dependent Oligomerization Of Fgf2 On Membranementioning
confidence: 99%
“…2A), we observed a dose-dependent calcein release from LUVs incubated with 3Ј,6-dinonyl neamine at concentrations ranging from 0.25 to 1.7 M. After the addition of 3Ј,6-dinonyl neamine at 1 M, Ͼ80% of calcein was released in the presence of cardiolipin, whereas only around 50% was released when cardiolipin was absent. These differences could reflect differences in mechanism (all-or-none versus graded mechanisms) (49), but further studies are required to confirm this. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 2 shows representative plots for GUVs treated with cyt c. An abrupt change of the interior plot from zero or minimal slope to a steep slope indicates the instant when leakage begins; this observation is interpreted as the opening of a lipid pore, corresponding to an all-or-none type of leakage described in literature (27). Behavior and event timing varied for GUVs within a single sample, implying that pore formation is a stochastic process, whereas initial binding of cyt c to the membrane was fast.…”
Section: Resultsmentioning
confidence: 99%